Synthesis and electrochemical performance of a single walled carbon nanohorn-Fe3O4 nanocomposite supercapacitor electrode - Deshmukh, Ashvini B.; Shelke, Manjusha V. (RSC Advances, 2013)
A new Fe3O4-SWCNH nanocomposite was synthesized as an electrode material for supercapacitors. The nanocomposite exhibited a high specific capacitance of 377 F g(-1) and delivered a stable discharge capacitance at a current density of 1 A g(-1) over 1000 cycles between 0 and 1.2 V.

Synthesis and electrochemical performance of a single walled carbon nanohorn-Fe3O4 nanocomposite supercapacitor electrode (vol 3, pg 21390, 2013) - Deshmukh, Ashvini B.; Shelke, Manjusha V. (RSC Advances, 2014)